Sulfide electrolyte layer for all-solid-state secondary battery, and all-solid-state secondary battery

By using a combination of copolymer binder and organic solvents of polyvinylidene fluoride structural units, the problem of unevenness of solid electrolyte layer in all-solid secondary batteries is solved, and a full-solid secondary battery with high efficiency and long cycle life is achieved .

CN119297376APending Publication Date: 2025-01-10QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410695291.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Uneven surface particle agglomerates are easily formed during the coating process of the sulfide solid electrolyte layer in an all-solid secondary battery, resulting in increased internal resistance of the battery and poor efficiency and cycle life.

Method used

Using a combination of a copolymer binder solution based on polyvinylidene fluoride structural unit and an organic solvent, a transparent binder solution is prepared by stirring and heating treatment to avoid the formation of agglomerates, and the active layer and solid are combined in the electrode. The sulfide solid electrolyte particles are fully dispersed in the electrolyte separator layer.

Benefits of technology

The high efficiency and good cycle life of all-solid secondary batteries are achieved, with the first round efficiency reaching more than 80%, and the capacity retention rate after 850 cycles is 80%.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

Provided is a sulfide solid electrolyte layer capable of forming an all-solid secondary battery which can exhibit excellent efficiency and cycle life. The sulfide solid electrolyte layer contains a sulfide solid electrolyte, a binder in the form of particles, and an organic solvent. And the sulfide solid electrolyte contains Li6PS5Cl. The binder comprises a copolymer binder based on a polyvinylidene fluoride structural unit, and the organic solvent is used for dissolving the copolymer binder based on the polyvinylidene fluoride structural unit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sulfide solid electrolyte layer for an all-solid secondary battery and an all-solid secondary battery. Background Art

[0002] In recent years, new energy electric vehicles have been vigorously cultivated and developed as a strategic industry in my country to ensure the realization of national energy security and low carbon emissions. As the core component of electric vehicles, lithium-ion batteries have become the mainstream energy storage devices for electric vehicles due to their high energy density, long cycle life, low self-discharge rate and no memory effect. However, in addition to the above advantages, lithium-ion batteries also have disadvantages that limit their large-scale market promotion, such as the safety of lithium-ion batteries that people are concerned about. Therefore, all-solid secondary batteries have attracted much attention because they contain solid electrolytes with low flammability and low fire hazard when leaked. All-solid secondary batteries include a positive electrode, a negative electrode and a solid electrolyte separator layer located between the positive and negative electrodes. The preparation method of the electrode of the all-solid secondary battery is: a slurry composition containing battery active materials (positive electrode active materials, negative electrode active materials), a binder solution, a conductive agent and a solid electrolyte is coated on the current collector, and the slurry composition on the current collector is dried to form an electrode composite active layer (positive electrode composite active layer, negative electrode composite active layer). The preparation method of the solid electrolyte diaphragm layer of the all-solid secondary battery is as follows: a slurry composition containing a sulfide solid electrolyte, binder particles and an organic solvent is coated on a Cu foil, and an ultra-thin diaphragm is formed after drying, and then an ultra-thin sulfide solid electrolyte layer is transferred on the electrode composite active layer by a flat plate hot pressing method. As a slurry composition for forming an all-solid secondary battery, a copolymer binder based on a polyvinylidene fluoride structural unit and an organic solution for dispersing the binder are used. Summary of the invention

[0003] Sulfide solid electrolytes are expected to become diaphragm materials for all-solid secondary batteries due to their high ionic conductivity. The diaphragm of the all-solid secondary battery is prepared by a slurry coating and drying method. That is, the sulfide solid electrolyte and the binder solution are stirred and mixed to prepare a slurry mixture of the diaphragm layer. The solid electrolyte slurry composition is coated on the surface of the electrode composite active layer and dried to form a diaphragm of the all-solid secondary battery. The present invention relates to a sulfide solid electrolyte layer that enables an all-solid secondary battery to exert excellent efficiency and cycle life. The sulfide solid electrolyte layer includes a sulfide solid electrolyte and a binder solution. The binder particles contain polymer materials. It contains a copolymer based on a polyvinylidene fluoride structural unit. One or more selected from polyvinylidene fluoride copolymers PVdF, polyvinylidene fluoride-hexafluoropropylene copolymers PVdF-HFP and polyvinylidene fluoride-trifluorochloroethylene PVdF-CTFE. The molecular weight is less than 500,000. The solvent contains one or more selected from diisobutyl ketone, butyl butyrate, isobutyl isobutyrate, anisole, n-decane and p-xylene. Particle agglomerates are easily formed in the slurry composition, and the agglomerates can be a composite of solid electrolyte and binder particles in the solid electrolyte slurry. Agglomerates in the slurry will make the surface granularity obvious during the coating process, resulting in an uneven solid electrolyte layer. The uneven coating thickness increases the internal resistance of the solid secondary battery, and the efficiency and cycle life are poor. The object of the present invention is to provide an ultra-thin sulfide solid electrolyte layer so that the all-solid secondary battery exhibits good efficiency and cycle life. DETAILED DESCRIPTION

[0004] Hereinafter, the embodiments of the present invention will be described in detail. The binder solution for all-solid secondary batteries of the present invention can be used when preparing the all-solid secondary battery electrode active material slurry composition and the solid electrolyte slurry composition of the present invention. The slurry composition for all-solid secondary batteries of the present invention can be used when forming the electrode composite active layer and the solid electrolyte layer of the solid secondary battery. (Binder solution for all-solid secondary batteries)

[0005] The binder solution of the present invention comprises binder particles and an organic solvent for dissolving the binder particles. The binder solution may, for example, be composed of less than 5% by mass of binder particles and the remaining amount of organic solvent. Thus, a binder solution with moderate fluidity and dispersibility is obtained. The binder solution may, for example, be composed of 1% to 5% by mass of binder particles and the remaining amount of organic solvent.

[0006] <<Organic Solvent>> The organic solvent is a liquid, serves as a dispersion medium, and may include one or more of diisobutyl ketone, butyl butyrate, isobutyl isobutyrate, anisole, n-decane, and p-xylene. The organic solvent may be composed of butyl butyrate, for example. Butyrate has a weak polarity and a low tendency to react with the sulfide solid electrolyte.

[0007] 《Binder particles》Binder particles are dispersed as dispersoids in an organic solvent serving as a dispersion medium. The binder particles can fully bond the components of the slurry composition for all-solid secondary batteries. The binder particles are basically composed of polymer materials. The polymer material contains a copolymer of polyvinylidene fluoride structural units. The "structural unit" in this embodiment refers to a part of the atomic group that constitutes the basic structure of the polymer material molecular chain. The polymer material can be, for example, a copolymer, and the polymer material can be, for example, a polyvinylidene fluoride copolymer PVdF, a polyvinylidene fluoride-hexafluoropropylene copolymer PVdF-HFP or a polyvinylidene fluoride-trifluorochloroethylene PVdF-CTFE, all of which contain polyvinylidene fluoride structural units, composed of (CH2CF2) n The molecular weight of the polymer material is measured, for example, by gel permeation chromatography. The polymer material may have, for example, an average molecular weight of less than 500,000. The polymer material may have, for example, an average molecular weight of 100,000 to 500,000.

[0008] 《Method for producing a binder solution》 The method for producing a binder solution of the present embodiment includes preparing a binder solution by fully mixing and dissolving an organic solvent and binder particles. Prepare an organic solvent as described above. Prepare binder particles as described above. Prepare a specified container, such as a glass container. Place a specified amount of binder particles and an organic solvent in a specified container. The mass percentage of the binder particles is relative to the total amount of the organic solvent and the binder particles, for example, it can be 1% by mass or more and 5% by mass or less. After placing the binder composition in the container, let it stand for a period of time, and the standing time can be, for example, more than 2 hours. The standing time can be, for example, less than 24 hours. The method for producing a binder solution of the present embodiment includes stirring the binder composition so that the binder particles are fully dissolved and dispersed. Stirring includes any stirrer and disperser. For example, the binder composition can be stirred by magnetic stirring. The temperature of the binder composition needs to be controlled during the stirring of the binder of the present embodiment. For example, the binder composition is stirred at a temperature of more than 100°C and less than 140°C. For example, the binder composition is stirred and heated to more than 100°C. After the temperature reaches above 100°C, continue stirring and keeping warm for a specified time so that the temperature does not exceed 140°C. The stirring and keeping warm time may be, for example, more than 10 minutes. The stirring and keeping warm time may be, for example, more than 20 minutes. The stirring and keeping warm time may be, for example, more than 60 minutes. The stirring and keeping warm time may be, for example, less than 120 minutes. By stirring and keeping warm the binder composition for a specified time, a fully dissolved and dispersed transparent binder solution is obtained. As a result, it will be difficult to form agglomerates when preparing a slurry for an all-solid secondary battery. (Slurry for all-solid secondary batteries)

[0009] The slurry for the all-solid secondary battery of this embodiment includes an electrode slurry composition and a sulfide solid electrolyte slurry composition. The electrode slurry composition includes the above-mentioned binder solution, electrode active materials (positive electrode active materials and negative electrode active materials), a conductive agent and a sulfide solid electrolyte. The sulfide solid electrolyte slurry composition includes the above-mentioned binder solution and a sulfide solid electrolyte. The electrode slurry composition is applied on the current collector and dried to form an electrode composite active material layer (positive electrode composite active material layer and negative electrode composite active material layer). The sulfide solid electrolyte slurry composition is applied on the electrode composite active material layer and dried to form a sulfide solid electrolyte separator.

[0010] [Positive electrode active material] The positive electrode active material for all-solid secondary batteries is not limited, and can be a compound that can absorb and release lithium ions, such as lithium composite metal oxides LiCoO2, LiNiO2, LiFePO4, LiNi x Mn y Co 1-x-y O2, LiMn2O4, or a mixture of at least two thereof. In order to improve the cycle characteristics of the all-solid secondary battery, the positive electrode active material is coated, for example, it can be LiNbO3 lithium metal oxide.

[0011] Negative electrode active material: The negative electrode active material for all-solid secondary batteries is not limited. For example, it can be a carbon allotrope such as graphite and coke, a carbon metal complex such as silicon carbon, a metal oxide such as silicon, silicon, tin, zinc, manganese, iron, nickel, etc., a metal such as lithium and silicon, a lithium alloy such as Li-Al, Li-Bi-Cd, Li-Sn-Cd, a lithium transition metal nitride, an organosilicon, etc.

[0012] Conductive agent: The conductive agent is not limited and can increase the conductivity. For example, it can be: acetylene black, carbon black, graphite and other carbon powders, various metal fibers, foils, etc.

[0013] 《Sulfide Solid Electrolyte》Sulfide solid electrolyte can be fully crushed and ground to obtain solid electrolyte particles with uniform particle size distribution. Solid electrolytes are not fixed in shape. In order to ensure the specific surface area of ​​the solid electrolyte, the particle size can be, for example, 0.3-50 μm to ensure the output characteristics of the all-solid secondary battery. The positive and negative active material slurry and the solid electrolyte slurry composition can use the same sulfide solid electrolyte. For example, it can be a crystalline inorganic lithium ion conductor, Li3N, LISICON (Li 14 Zn(Ge04)4), perovskite-type Li 0.5 La 0.5 TiO3、LIPON(Li 3+y PoO 4-X N X)、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc. For example, it can be an amorphous inorganic lithium ion conductor, Li-Si-S-0, Li-PS etc. Preferably, the sulfide solid electrolyte Li6PS5Cl. The lithium ion conductivity of the sulfide solid electrolyte for all-solid secondary batteries is 10 -4 S / cm or more.

[0014] 《Binder solution》 The binder solution prepared by the above method can be used to prepare electrode active material slurry and sulfide solid electrolyte slurry. The content of binder particles in the electrode active material slurry composition and the sulfide solid electrolyte slurry composition can be, for example, 1% by mass or more and 10% by mass or less relative to 100 parts by mass of the electrode active material slurry composition and the solid electrolyte slurry composition. The components in the slurry composition are fully bonded and the transport performance of lithium ions is ensured.

[0015] The positive electrode active material slurry composition of the all-solid secondary battery can be obtained by fully dispersing and mixing the above-mentioned positive electrode active material, sulfide solid electrolyte particles, conductive agent, and binder solution. The sulfide solid electrolyte particles are in full contact with the positive electrode active material to ensure that the positive electrode composite active material layer has good lithium ion transmission after drying. The conductive agent ensures good conductivity.

[0016] 《Negative electrode active material slurry》 The negative electrode active material slurry composition of the all-solid secondary battery can be obtained by fully dispersing and mixing the above-mentioned negative electrode active material, sulfide solid electrolyte particles, conductive agent, and binder solution. The sulfide solid electrolyte particles are in full contact with the negative electrode active material to ensure that the negative electrode composite active material layer has good lithium ion transmission after drying. The conductive agent ensures good conductivity. The mass percentage of the solid electrolyte contained in the electrode active material slurry composition is relative to the total mass of the electrode active material, conductive agent, solid electrolyte and binder particles, for example, it can be more than 10% by mass and less than 70% by mass, which can fully ensure lithium ion conductivity, effectively and fully contact the electrode active material, and fully increase the capacity of the all-solid secondary battery.

[0017] Sulfide solid electrolyte slurry The sulfide solid electrolyte slurry of the solid secondary battery can be obtained by fully dispersing and mixing the above-mentioned sulfide solid electrolyte particles and the binder solution. The use of the above-mentioned binder solution can inhibit the formation of slurry agglomerates, so that the all-solid secondary battery can exert excellent output characteristics.

[0018] 《Method for preparing slurry for all-solid secondary battery》 The electrode active material slurry composition and the solid electrolyte slurry composition are obtained by fully dispersing and mixing the above-mentioned components. The dispersion mixing method can use, for example, stirring, oscillating and rotating mixing devices. Examples include the use of dispersing devices such as homogenizers, ball mills, bead mills, sand mills, roller mills and planetary mixers. Thereby, the agglomeration of the electrode active material and the solid electrolyte slurry is suppressed. Preferably, a planetary mixer is used to break up the slurry agglomerates. A stirring method, which includes low-speed stirring, high-speed stirring and low-speed vacuum stirring; the speed of the low-speed stirring is less than 600 rpm. The speed of the high-speed stirring is higher than 2000 rpm. (Method for manufacturing all-solid-state secondary battery)

[0019] The manufacturing method of the all-solid secondary battery of this embodiment includes the preparation of electrode slurry and sulfide solid electrolyte slurry for the all-solid secondary battery, the electrode slurry is coated on the collector and dried to form an electrode composite active layer, the solid electrolyte is coated on the electrode composite active layer and dried to form a solid electrolyte membrane, and the positive and negative composite active layers contain a solid electrolyte membrane to compress and assemble the battery.

[0020] "Current Collector" The current collector for all-solid secondary batteries needs to have a material with good conductivity and electrochemical tolerance, for example, it can be a metal material such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, molybdenum, etc. Among them, aluminum is preferably used as the positive electrode current collector, and copper is preferably used as the negative electrode current collector. The shape of the current collector is not particularly limited, for example, it can be a foil-shaped current collector with a thickness of more than 0.001 mm and less than about 0.5 mm. In order to improve the bonding strength and conductivity of the current collector and the electrode composite active material layer, an intermediate layer can be formed on the surface of the current collector, for example, a carbon coating can be performed.

[0021] 《Preparation Method of Positive Electrode Composite Active Material Layer》 The preparation of the positive electrode composite active material layer is carried out by coating the above-mentioned positive electrode composite slurry composition on the positive electrode current collector and drying to form a positive electrode composite active material layer. The coating method may be, for example, a doctor blade method, an immersion method, a reverse roll coating method, a direct roll coating method, a gravure printing method, an extrusion method, a brush coating method, etc. The drying method may be, for example, drying with warm air, hot air, or low-humidity air, vacuum drying, or drying with irradiation methods such as (far) infrared rays and electron beams. Drying should ensure that cracks are not generated in the positive electrode composite active material layer and that the positive electrode composite active material layer is not peeled off from the current collector. The drying temperature may be, for example, higher than 50°C and lower than 130°C, and the drying time is not particularly limited, and may be, for example, more than 60 min and less than 240 min.

[0022] 《Method for preparing negative electrode composite active material layer》 The preparation of the negative electrode composite active material layer is carried out by coating the above-mentioned negative electrode composite slurry composition on the negative electrode current collector and drying to form a negative electrode composite active material layer. The coating method may be, for example, a doctor blade method, an immersion method, a reverse roller coating method, a direct roller coating method, a gravure printing method, an extrusion method, a brush coating method, etc. The drying method may be, for example, drying with warm air, hot air, or low-humidity air, vacuum drying, or drying with irradiation methods such as (far) infrared rays and electron beams. Drying should ensure that cracks are not generated in the negative electrode composite active material layer and that the negative electrode composite active material layer is not peeled off from the current collector. The drying temperature may be, for example, higher than 50°C and lower than 130°C, and the drying time is not particularly limited, and may be, for example, more than 60 min and less than 240 min.

[0023] 《Preparation method of solid electrolyte diaphragm layer》 The preparation of the solid electrolyte diaphragm layer is carried out by coating the above-mentioned solid electrolyte slurry composition on Cu foil and drying to form a solid electrolyte diaphragm layer. The coating method may be, for example, a doctor blade method, an immersion method, a reverse roll coating method, a direct roll coating method, a gravure printing method, an extrusion method, a brush coating method, etc. The drying method may be, for example, drying with warm air, hot air, or low-humidity air, vacuum drying, or drying with irradiation methods such as (far) infrared rays and electron beams. Drying should ensure that cracks are not generated in the solid electrolyte diaphragm layer and that the solid electrolyte diaphragm layer is not peeled off from the electrode composite active material layer. The drying temperature may be, for example, higher than 50°C and lower than 130°C, and the drying time is not particularly limited, and may be, for example, more than 60 min and less than 240 min. The diaphragm is transferred by flat hot pressing, and the Cu foil coated with the diaphragm and the positive and negative electrode plates are buckled with appropriate pressure and temperature, and kept at appropriate pressure and temperature for a period of time. After the pressure is released, the Cu foil is peeled off, and the diaphragm is covered on the surface of the positive and negative electrodes; the all-solid secondary battery of the present invention can be obtained by the following method: the positive electrode and the negative electrode are stacked in a relative manner with the positive electrode composite active material layer and the negative electrode composite active material layer separated by the solid electrolyte diaphragm layer, and pressurized arbitrarily. After obtaining the stacked body, according to the shape of the battery, keep the existing state or wind, fold, etc. and put it into the battery container for sealing. In addition, porous metal mesh, fuse, PTC element and other overcurrent protection elements, guide plates, etc. can also be placed in the battery container as needed to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be any shape such as coin, button, sheet, cylindrical, square, flat, etc.

[0024] Examples: The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0025] <Preparation of Binder Solution> To 19 parts of butyl butyrate organic solvent, 1 part of polyvinylidene fluoride PVdF was added, heated to 100° C., and magnetically stirred for 60 min to obtain a binder solution.

[0026] <Preparation of positive electrode active material layer slurry> Mix 65 parts of positive electrode active material lithium cobalt oxide, 30 parts of solid electrolyte Li6PS5Cl, 2.5 parts of conductive agent graphite and 2.5 parts of conductive agent conductive carbon fiber, mix in 3 parts of a binder composition in terms of solid content, and then add butyl butyrate as an organic solvent to adjust the solid content concentration to 40%, and then mix in a planetary mixer for 60 minutes to prepare a slurry composition for a positive electrode active material layer.

[0027] <Preparation of negative electrode active material layer slurry> Mix 60 parts of negative electrode active material graphite, 35 parts of solid electrolyte Li6PS5Cl and 5 parts of conductive agent conductive carbon fiber, mix in 3 parts of a binder composition in terms of solid content, and then add butyl butyrate as an organic solvent to adjust the solid content concentration to 35%, and then mix in a planetary mixer for 60 minutes to prepare a slurry composition for the negative electrode active material layer.

[0028] <Preparation of solid electrolyte diaphragm layer slurry> Mix 100 parts of solid electrolyte Li6PS5Cl and 2 parts of a binder composition in terms of solid content, then add butyl butyrate as an organic solvent to adjust the solid content concentration to 50%, and then mix in a planetary mixer for 60 minutes to prepare a slurry composition for a solid electrolyte diaphragm layer.

[0029] <Manufacturing of all-solid secondary batteries> The positive and negative active material layer slurry is coated on the positive and negative current collectors by a scraper method, the scraper thickness is 200 μm, and it is dried at 80 ° C for 30 min to form an electrode composite active material layer with a thickness of about 100 μm. The above-mentioned solid electrolyte slurry composition is coated on the Cu foil and dried to form a solid electrolyte diaphragm layer. The scraper thickness is 100 μm, and it is dried at 80 ° C for 30 min to form a solid electrolyte diaphragm layer with a thickness of about 30 μm. The Cu foil coated with the diaphragm and the positive and negative electrode plates are buckled with appropriate pressure and temperature, and maintained at appropriate pressure and temperature for a period of time. After the pressure is released, the Cu foil is peeled off, and the diaphragm is covered on the surface of the positive and negative electrodes. The pressure is less than 40MPa, the temperature is less than 60 ° C, and the time is less than 30min. The positive composite active material layer and the negative composite active material layer of the all-solid secondary battery with a solid electrolyte diaphragm layer are laminated and pressed to obtain an all-solid secondary battery. The first-cycle efficiency of the pressed all-solid-state secondary battery reached over 80%, with a capacity retention rate of 80% after 850 cycles.

Claims

1. A sulfide solid electrolyte layer for all-solid-state batteries.

2. The sulfide solid electrolyte layer according to claim 1, comprising a sulfide solid electrolyte, a particle binder and an organic solvent.

3. The sulfide solid electrolyte according to claim 2, comprising Li6PS5Cl.

4. The particle binder according to claim 2, comprising: Copolymer binder based on polyvinylidene fluoride structural units.

5. The copolymer binder based on polyvinylidene fluoride structural units according to claim 4, comprising one or more selected from polyvinylidene fluoride copolymer PVdF, polyvinylidene fluoride-hexafluoropropylene copolymer PVdF-HFP and polyvinylidene fluoride-chlorotrifluoroethylene PVdF-CTFE.

6. The method according to claim 4, wherein the average molecular weight of the copolymer binder based on polyvinylidene fluoride structural units is less than 500,000.

7. The organic solvent according to claim 2, wherein the solvent comprises one or more selected from diisobutyl ketone, butyl butyrate, isobutyl isobutyrate, anisole, n-decane and p-xylene.

8. A method for producing a binder solution, comprising: mixing a solvent and binder particles to prepare a binder solution, and stirring the binder solution to dissolve the binder particles; The binder solution is stirred while being maintained at a temperature of 100° C. or higher and 140° C. or lower.

9. The method for producing a binder solution according to claim 8, wherein: The binder solution was stirred using magnetic stirring.

10. A method for manufacturing an all-solid secondary battery, comprising: Mixing and stirring the binder solution according to claim 2 or 8 and the sulfide solid electrolyte to prepare a slurry composition; Stirring and breaking up the agglomerates contained in the slurry composition; After the agglomerates are broken up, the slurry composition is applied to the surface of the Cu foil and dried to form a diaphragm; The separator is transferred to the surface of the positive and negative electrode active layers by transfer method.

11. The membrane transfer method according to claim 11, wherein: The diaphragm is transferred by flat-plate hot pressing; The flat plate hot pressing comprises buckling the Cu foil coated with the diaphragm and the positive and negative electrode sheets with appropriate pressure and temperature, maintaining the appropriate pressure and temperature for a period of time, and removing the Cu foil after the pressure is released, so that the diaphragm covers the positive and negative electrode surfaces; The pressure is lower than 40MPa; Temperature below 60°C; The time is less than 30 minutes.